The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jmv.21879
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C infection, Cognition, and inflammation in an Egyptian sample

Abstract: Chronic hepatitis C (HCV) infection is associated with cognitive impairments which might be mediated through a secondary inflammatory cascade. Egypt has an unusually high prevalence of HCV monoinfections and is an ideal site for the study of the isolated effects of HCV infection. Therefore, in a hospital-based cross-sectional study based in Egypt, this study compared cognitive functioning and serum markers of inflammation in 11 HCV positive cases and 14 HCV negative controls. The Wisconsin Card Sorting Test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…19 The cognitive impairment observed in this particular study group could also have been due to non-HIV comorbid infections or conditions. Hepatitis C infection is one such condition but it is rare among HIV-positive individuals in Uganda, with a prevalence of 3%, 20,21 and thus an unlikely cause for the observations made. Tuberculosis with CNS involvement can affect the level of consciousness and consequently the level of cognitive function.…”
Section: Resultsmentioning
confidence: 99%
“…19 The cognitive impairment observed in this particular study group could also have been due to non-HIV comorbid infections or conditions. Hepatitis C infection is one such condition but it is rare among HIV-positive individuals in Uganda, with a prevalence of 3%, 20,21 and thus an unlikely cause for the observations made. Tuberculosis with CNS involvement can affect the level of consciousness and consequently the level of cognitive function.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated increased expression of and serum levels of IL‐6, TNF‐ α, sTNFR, sCD163, and sCD14 among CHC patients compared to healthy controls (Table ) and those with other hepatic diseases such as alcoholic liver disease . In addition, increased serum levels of IL‐10, or disturbances in the ratios of proinflammatory/anti‐inflammatory cytokines TNF‐α/IL‐10 and IL‐6/IL‐10 have been noted among CHC patients compared to healthy controls .…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis by type of illicit drug use or HCV co-infection did not show significant differences in plasma or CSF sCD14, CCL2, or IL-6, consistent with other studies that failed to demonstrate associations between these comorbidities and elevated sCD14 or CCL2. 5, 54 Thus, these comorbidities are unlikely to account for associations between elevated sCD14 and impaired global T scores. The study cohort was from NNTC, which specifically recruits individuals with advanced disease, and CHARTER, which includes a large population of well-controlled HIV+ subjects, to represent a diverse population of HIV-infected individuals with broad range of viral loads.…”
Section: Discussionmentioning
confidence: 99%